Learning analytics through a digital game-based learning environment - Cariaga, Ada Angeli D. (College of Engineering, University of the Philippines Diliman, 2015)
Game-based learning has been considered in different studies as a supplementary tool if not an alternative tool for traditional classroom learning. Game-based learning (GBL), together with Personalized Learning Environment (PLE) and Learning Management Systems (LMS), are part of the digital learning environment where there is an increasing demand of converting, translating, interpreting and presenting learning-related data for different kinds of analysis -- learning analytics. Learning environments such as PLEs and LMSs are the common source of these data but another rich data source is the GBL environment. Data from GBL environment are often under collected if not uncollected therefore not translated and analyzed properly. This research proposes a learning analytics framework applied to a digital GBL environment to be able to materialize their relationship. The proposed framework includes a way to capture, translate, present and share data from different game events that may contribute in the learning process. The research also includes a proof-of-concept implementation using iOS as the game platform and the built in Game Center of iOS for presentation of the data collected. The proposed framework and data presentation through the Game Center received a positive feedback from the stakeholders -- learners and educators.